Oil Palm Agroforestry Can Achieve Economic and Environmental Gains as Indicated by Multifunctional Land Equivalent Ratios - Khasanah, N.; Noordwijk, M. van; Slingerland, Maja; Sofiyudin, M.; Stomph, D.; Migeon, A.F.; Hairiah, K. (Frontiers Media, 2020)
Driven by increased global demand for vegetable oil in the food and biofuel sectors, oil palm plantations based on monoculture technology have expanded into lowland tropical forests. Interest in diversified, mixed oil palm systems is increasing as these might increase efficiency of the use of land and other resources, reduce farmer risk, and decrease greenhouse gas (GHG) emissions per unit product. Land Equivalent Ratio for provisioning services (LERP) values above 1.0 show that at least some diversified systems use land more efficiently than monocultures and are thus “land sparing,” where monoculture LERP cannot exceed 1.0. Diversification also modifies climate and water regulating functions (“land sharing”) relative to a forest reference, as indicated in the LERR index. A “multifunctional” LERM indicator combines both